(untitled) (Fiep Bulletin - online, 2020)
According to IBGE, the age group of the population had a significant increase from 2012, where life expectancy in 1940 was 45.5, and in 2018 is 76.2 years in men and 79.8 years in women. The way that the elderly are seen and treated by society ends up giving a non-real image, because old age began to be treated as a stage of life characterized by physical decay and absence of social roles from the second half of the nineteenth century. This research intends to contribute to the analysis of how the current society sees and treats the old age, and trying to answer questions of if the prejudice exists, and what it represents to be "old" in the conception of these elderly. The methodology to be used is qualitative and quantitative. Based on the literature review, historical data, and the application of a small WHOQOL-bref questionnaire adapted for the elderly, to be answered by older people from 60 years old. Selected and qualitatively articulated bibliographies. This information will be analyzed to dialogue with the official documentation in the investigation, privileged to explain the social historical process of the elderly. The results show that seniors have autonomy, and have active social participation, and that age does not prevent them from accomplishing what they want efficiently.